PERANAN PEMERINTAH DAN PARTISIPASI MASYARAKAT TERHADAP PEMBERDAYAAN GENERASI MUDA DI KELURAHAN KADIDI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Ahyar Ahyar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
The purpose of research is to determine the role of government and public participation in the Empowerment of Youths in Sub Kadidi District of Panca Chert Sidenreng Rappang, and to determine the factors that affect the role of government and public participation in the Empowerment of Youths in Sub Kadidi District of Panca Chert Sidenreng Rappang The population of this study were 1264 young people, while the sample using the formula Slovin where samples are taken amounted to 93 youth. Data collection techniques used in this research is to use the technique (1) observation, (2) Interviews (3) questionnaire, and (4) Study Library. The collected data was then analyzed using frequency tables and percentages. The results of this study indicate that the indicator of the government's role in the Village Youths Empowerment Kadidi District of Panca Chert Sidenreng Rappang with a value of 69.25% instrumental categories, indicators of the Empowerment Community Participation Youths in Sub District of Panca Chert Kadidi Sidenreng Rappang with a value of 70% the instrumental categories, indicators of empowerment of youth in the Village District of Panca Chert Kadidi Sidenreng Rappang with a value of 68.6% to the category of acts and the factors that influence the Government's role in the Village Youths empowerment Kadidi District of Panca Chert Sidenreng Rappang with a score of 69 %, and the factors that influence the participation of the community in the Village Youths Empowerment KadidiDistrict of Panca Chert Sidenreng Rappang with a value of 69.67% with a role category.